SOME OBSERVATION ON LINEAGE OF KING CHANDRABANU OF TAMBRALINGA - Suvajo, Phramaha Pochana (JOURNAL OF HUMANITIES AND SOCIAL SCIENCES SONGKHLA RAJABHAT UNIVERSITY, 2022)
The objective of this academic article is to study linage of King Chandrabanu of Tambralinga. This article focuses on 3 issues; 1) a descendent from Kalinga dynasty in the Malay Peninsula, 2) a descendent from the Kalinga dynasty in India and 3) a descendent from the Sri Dhammasokarat dynasty in Nakhon Si Thammarat. The result shows that a descendent of King Chandrabanu from Kalinga dynasty in the Malay Peninsula is supported by inscriptions in Sri Lanka and Thailand. A descendent from the Kalinga dynasty in India is evident in Sri Lanka’s texts and Tamil inscription. And a descendent from the Sri Dhammasokarat dynasty in Nakhon Si Thammarat is assured by Thai scholars which supported from texts and inscriptions. It is interesting to note that the name of King Chandrabanu and Sri Dhammasokarat dynasty are well-known as public names. Those do not specially mention anyone. It is known as king of southern kingdom of Thailand in ancient time.